BENTUK-BENTUK PENGAKUAN DALAM HUKUM INTERNASIONAL - Aisyah, Nur; Rizaldy, Putri Zalianty; Maryati, Anggun; Surandi, Surandi; Guspita, Devika Rosa (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2026)
Recognition in international law is a fundamental concept that determines the legal standing of a country or new government in international relations. This article aims to analyze the meaning, forms, functions, and impacts of recognition in international law. The research method used is normative legal research with a regulatory and conceptual approach. The results of the study indicate that recognition can be classified into several forms, namely: (1) de facto recognition which is temporary in nature based on factual reality; (2) de jure recognition which is full and official according to international law; (3) explicit recognition through official statements; (4) implied recognition through certain acts of thought or cooperation; and (5) collective recognition given together through international organizations such as the United Nations. The conditions for the formation of a state as stipulated in the 1933 Montevideo Convention, namely territory, people, government, and the ability to establish international relations, are the main benchmarks in granting recognition. Recognition serves to provide international legitimacy, open diplomatic relations, and enable a country’s active participation in international organizations. Without recognition, a country faces serious challenges in the political, economic, and diplomatic fields